The Influence of Muslim Fashion Awareness and Its Factors on Muslim Fashion Consumption In Indonesia - Prasetika, Intan; Ridanasti, Erlita (International Journal of Social Research, 2024)
This research aims to determine and analyze the influence of knowledge sources, Muslim fashion motivation, clothing style, and the uniqueness of Muslim fashion on Muslim fashion consumption through Muslim fashion awareness. The method used in this research uses the SEM PLS method which analyzes the influence of knowledge sources, Muslim fashion motivation, clothing style, and the uniqueness of Muslim fashion on Muslim fashion consumption through Muslim fashion awareness. The results of this research show that Muslim Fashion Awareness produces a positive and significant influence on Fashion Consumption, Muslim Fashion Knowledge Sources produce a positive and significant influence on Fashion Consumption. Muslim Fashion Motivation produces a positive and significant influence on Fashion Consumption, Dress style produces a positive and significant influence on Fashion Consumption, and the uniqueness of Muslim Fashion produces a positive and significant influence on Fashion Consumption